Analysis of Top 50 Tamil Item Number Lyrics in the Spotify App - M, Saranya (Journal of Advanced Research in Journalism & Mass Communication, 2023)
This study focuses on top 54 Tamil item number lyrics from Spotify app. This research is based on quantitative content analysis method and it was used to find out the most used words in Tamil item number lyrics. Data was collected on 54 item number song, Name of the lyricist, Name of the Movie and the year with the 15 variables. The researcher used the sexual desire theory for this paper. Thus, the researcher finds women are portrayed in negative way as an objectification and there are 205 metaphor words. The analysis includes the 54 item number lyrics are portraying the women as an objectification. Indian cinema an item number or item song is a musical number inserted into a film that may or may not have any relevance to the plot. Item song lyrics; Comparing objects, fruits, animals to various parts of the body, most used words, gender specification (male and female) in the item songs. How to cite this article: Saranya M. Analysis of Top 50 Tamil Item Number Lyrics in the Spotify App. J Adv Res Jrnl Mass Comm 2023; 10(2): 1-7. DOI: https://doi.org/10.24321/2395.3810.202308